تأثير تمرينات مركبة في تطوير بعض خصائص منحنى قوة - زمن لمهارة الضرب الساحق القطري للشباب بالكرة الطائرة - مشجل، نصر الله راضي (جامعة بابل - كلية التربية الرياضية, 2023)
هدفت الدراسة إلى إعداد تمرينات مركبة لتطوير منحنى القوة - الزمن لتطوير مهارة الضرب الساحق القطري بالكرة الطائرة، والتعرف على الفروق الإحصائية بين الاختبارين القبلي والبعدي للمجموعتين الضابطة والتجريبية لمنحنى قوة - زمن المتغيرات المهارة الضرب الساحق القطري بالكرة الطائرة، والتعرف على الفروق الإحصائية بين المجموعتين الضابطة والتجريبية في الاختبار البعدي لبعض خصائص منحنى قوة - زمنة لمهارة الضرب الساحق القطري بالكرة الطائرة، أما منهج البحث أعتمد الباحث المنهج التجريبي بتصميم المجموعتين المتكافئتين (التجريبية والضابطة)، اشتمل مجتمع البحث على اللاعبين الشباب في المركز التخصصي بالكرة الطائرة في قضاء الجبايش الذين تتراوح أعمارهم من 16 -18 سنة للموسم (2021 -2022) والذين يمثلون فئة الشباب وعددهم (30) لاعبا، تم اختيار (5) لاعبين للعينة الاستطلاعية وتم اختيار (12) لاعبا يمثلون عينة البحث وبنسبة (40%) من المجتمع الأصلي، وتم تقسيم العينة إلى المجموعتين الضابطة والتجريبية بالطريقة العمدية لضمان توزيع اللاعبين على المجموعتين حسب الأطوال ومراكز اللعب وكل مجموعة تحتوي على (6) لاعبين، ومن أهم الاستنتاجات أن استخدام التمرينات المركبة أعطى صورة واضحه عن أفضليته من البرنامج التقليدي وذلك من خلال النتائج التي أظهرتها المجموعة التجريبية وأفضليتها عن المجموعة الضابطة، ومن أهم التوصيات باعتماد التمارين المركبة في الوحدات التدريبية لما لها من أثر فعال في بعض خصائص منحنى قوة زمن المهارة الضرب الساحق القطري بالكرة الطائرة. The study aimed to prepare compound exercises to develop the force-time curve to develop the skill of crushing diagonal hitting with volleyball, and to identify the statistical differences between the pre and post tests for the control and experimental groups of the curve of force-time variables for the skill of crushing diagonal hitting with volleyball, and to identify the statistical differences between the control and experimental groups In the post-test for some characteristics of the force-time curve for the skill of crushing the country with volleyball. As for the research approach, the researcher adopted the experimental approach by designing the two equal groups (experimental and control). - 18 years old for the season (2021-2022), who represent the youth category and their number is (30) players. (5) players were selected for the survey sample, and (12) players representing the research sample were selected (40%) from the original community, and the sample was divided into two groups The control and experimental method in the intentional way (to ensure the distribution of players in the two groups according to heights and playing positions) and each group contains (6) players, and one of the most important conclusions is that the use of compound exercises gave a clear picture of its preference over the traditional program, through the results shown by the experimental group and its preference over the group The control, and one of the most important recommendations is to adopt compound exercises in the training units because of their effective impact on some characteristics of the strength-time curve for the skill of crushing the diagonal volleyball.
Keywords: كرة الطائرة -- مهارة الضرب الساحق القطري -- الأداء المهاري -- الألعاب الرياضية